Exploring sleep-related disorders in patients with multiple sclerosis: A questionnaire-based approach - Ahmed K. Bamaga; Awatif Aljohani; Osama Y. Muthaffar; Anas S. Alyazidi; Sarah Y. Bahowarth; Nouf A. Almasry; Danya Y. Bakhsh (Journal of Family Medicine and Primary Care, 2024)
Background: Multiple sclerosis (MS) is considered the most prevalent neurological disorder in young adults with many patients manifesting sleep-related disorders (SRD) due to its pathomechanisms. This is subsequently reflected in patients’ quality of life and physical activities. Material and Methods: This is a cross-sectional study at a tertiary care center. Patients diagnosed with MS were enrolled, and assessment of their sleep patterns and related disorders were measured using pre-validated scales. A questionnaire consisting of 38 items was used, and the obtained data were analyzed using RStudio software. Results: A total of 260 patients participated in the study. Most participants were aged 31–40 (n = 112) with a mean age of 36.49 ± 8.41 (age range: 18–56 years). The most used medications were rituximab (27%) and ocrelizumab (25%). Shapiro–Wilk Test was significant (P = 0.04) and just below the significance level of α = 0.05, suggesting potential significant deviation in the distribution of age. Logistic regression model was applied, and the female probability of sleeping more than six hours was 3.60 times the probability of sleeping six hours or less. Conclusion: Sleep quality is multifaceted and requires intensive investigation in patients with chronic disorders including MS. In this study, several novel data have been presented in a population that has very little literature data.